Sexual Abuse Prevalence Rates of Residents in Institutional Care Settings Compared with a Population Representative Sample. Issue 4 (2nd October 2018) - Allroggen, Marc; Ohlert, Jeannine; Rau, Thea; Fegert, Jörg M.
ABSTRACT: Adolescents in residential institutions are considered to be a high-risk group for experiencing sexual abuse. The aim of this study was to provide a comparison of sexual abuse lifetime prevalence rates between residents in institutional settings and the general population. In total, 271 adolescents from 32 different institutions took part in the survey. Overall, 5.9% of the participants had experienced exhibitionism and 7.0% vaginal/anal penetration. Compared with the general population, significantly higher prevalence rates were evident for penetration. It has to be discussed whether population representative surveys should explicitly include these high-risk groups in order to avoid underestimating sexual abuse.